Correlation between Fluoride in Drinking Water and Its Levels in Breast Milk in Golestan Province, Northern Iran. - Hossein Faraji; Ali Akbar Mohammadi; Behrouz Akbari-Adergani; Naimeh Vakili Saatloo; Gholamreza Lashkarboloki; Amir Hossein Mahvi (Tehran University of Medical Sciences, 2014)
Fluoride is an essential element for human health. However, excess fluoride in drinking water may cause dental and/or skeletal fluorosis. Drinking water is the main route of fluoride intake. The aim of the present study was to measure fluoride levels in human breast milk collected from two regions of Golestan Province, northern Iran with different amount of fluoride concentration of drinking water in Bandar Gaz and Nokande cities and to correlate it with fluoride concentrations in drinking water used by mothers living in these two areas.Twenty samples of water were collected from seven drinking water wells during 2012 from Bandar Gaz and Nokande in Iran during 2012. Fluoride concentration of water samples was measured using SPADNS method. Sixty breast milk samples were collected from lactating mothers of Bandar Gaz and Nokande cities. Content in breast milk was determined using standard F ion-selective electrode. Spearman's rho correlation analysis was used to assess any possible relationship between fluoride levels in breast milk and in drinking water.The means and standard deviation for F concentration in breast milk and drinking water were 0.002188±0.00026224 ppm and 0.5850±0.22542 ppm, respectively. Analysis of data showed that the variables were not normally distributed so the Spearman correlation coefficient between two variables calculated (ρ S = 0.65) and it was significant (P=0.002).Fluoride concentration in water can directly act on its concentration in breast milk. We speculate that modifying F concentration in water can affect accessibility of fluoride for infants.